An Investigation into the Response of GFRP-Reinforced Glue-Laminated Tudor Arches - S. Alshurafa; H. Alhayek; F. Taheri (Advances in Civil Engineering)
This paper presents the results of an experimental and computational investigation tailored to examine the response of glass fiber-reinforced-plastic-(GFRP-) reinforced glue-laminated curved beams and arches. The main objective was to ascertain the viability of GFRP as an effective reinforcement for enhancing the load carrying capacity and stiffness of such curved structures. The study included optimization of the length and thickness of the GFRP reinforcement. In doing so, first a parametric finite element study was conducted to evaluate the influence of unidirectional GFRP reinforcement applied onto the arch using eleven possible configurations and different thicknesses. Subsequently, an experimental investigation was conducted to verify the results established by the finite element method as well as the integrity of actual GFRP-reinforced glue-laminated curved structures. The results indicate that GFRP can be considered as an effective and economically viable solution for strengthening and stiffening glulam arches, without adding any appreciable weight to the structure.